Self-managed working time and firm performance: Microeconometric evidence - Michael Beckmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper empirically examines the impact of self-managed working time (SMWT) on firm performance using panel data from German establishments. As a policy for the decentralization of decision rights, SMWT provides employees with extensive control over scheduling individual working time. From a theoretical viewpoint, SMWT has ambiguous effects on both worker productivity and wages. Based on the construction of a quasi-natural experiment and the combination of a differences-in-differences approach with propensity score matching as an identification strategy, the empirical analysis shows that up to five years after introduction, SMWT increases firm productivity by about 9% and wage costs by about 8.5%. This implies that SMWT improves both individual and firm productivity, and supplemental evidence shows that these productivity enhancements can primarily be explained by incentive effects associated with decentralization policies in general.
Keywords: M50; J81; J24; 330